(untitled) (Libellarium: journal for research in the field of information and related sciences, 2011)
The aim of the paper, deriving from David G. Mick, James E. Burroughs, Patrick Hetzel and Mary Y. Brannen’s (2004) theoretical approach, is to analyse whether the theories on marketing semiotics are applicable in the medieval context as well, i.e. if it could be said that Constantine - Cyril the Philosopher applied marketing semiotics in creating and promoting the Glagolitic script, i.e. the idea of Christianity, in the 9th century. The authors briefly remind of the development of semiotics and mention some relevant theories on marketing semiotics, review several theories on the origins of the Glagolitic script and then apply the above theories on Glagolitic graphemes and the script system as a whole. Constantine - Cyril the Philosopher’s curriculum vitae imposes the assumption that his mission was qualified by all the rules of marketing communications - by the creation of the Glagolitic script, Constantine - Cyril the Philosopher promoted the idea of Christianity embedded in the visual identity of each individual sign (and all the signs ordered into azbuka sequence) almost ‘following’, or better to say, anticipating the guidelines of the nowadays acknowledged theory on the rules of efficient marketing communications. The authors postulate the hypothesis that Glagolitic letters - graphemes, are powerful, arbitrary signs, the arbitrariness of which Constantine - Cyril encoded with a view to accomplishing the goals of his mission.